Scintillation properties of pure and Ca-doped ZnWO4 crystals - Danevich, F; Henry, S; Kraus, H; McGowan, R; Mikhailik, V; Shkulkova, O; Telfer, J (2008)
Following the investigations of the structure and scintillation properties of Ca-doped zinc tungstate powder [phys. stat. sol. (a) 204. 730 (2007)] a single-crystal of ZnWO4-Ca (0.5 mol%) was grown and characterised. The relative light output, energy resolution and decay characteristics were measured for pure and Ca-doped ZnWO4 scintillators. An increase in the light yield of ~40% compared with the undoped crystal, and an energy resolution 9.6% (137Cs) were obtained for Ca-doped ZnWO4. The observed improvement is attributed to the reduction of self-absorption (bleaching) of the crystal. The cause of bleaching as well as the possible contribution of scattering is discussed. © 2008 WILEY-VCH Verlag GmbH and Co. KGaA.